Trophic State of Cibanten Watershed - Muta Ali Khalifa; Forcep Rio Indaryanto (Jurnal Perikanan dan Kelautan, 2018)
Cibanten watershed upstream is from Karang Mount (one of that is shallow lake Cibanten water springs), flow in Serang City and the downstream at Banten Bay. From upstream until downstream, Cibanten watershed used by various anthropogenic activities where potentially to increasing trophic state of the waters. This research aimed to evaluate trophic state of Cibanten watershed. Research conducted at April – Mei 2018. Water sample took and measured at three different location, upstream (code: Hu), Central (code: T) and downstream (code: Hi). Water parameters where in-situ measurement was water depth, temperature, secchi depth, water colour, pH, dissolved oxygen and salinity (special for downstream). Water sample analysed at Aquaculture Laboratory of UNTIRTA, the water parameter was phosphate and chlorophyll-a. Trophic state of Cibanten watershed analysed with Trophic State Index (TSI). The result from upstream of Cibanten watershed categorized as mesotrophic, with maximum secchi depth until water bottom and existed some water plant. In the central and downstream of Cibanten watershed categorized as light eutrophic. The significant different between upstream, central and downstream of Cibanten watershed is secchi depth. Low secchi depth at central and downstream due to water turbidity, shown by water colour is yellowbrown that assumed come from suspended solid contents.